Effects of Vaccination with Lentogenic Vaccine and Challenge with Virulent Newcastle Disease Virus (NDV) on Egg Production in Commercial and SPF Chickens - Bwala , D.G.; Fasina, F.O.; Wyk, A. Van; Duncan, N.M. (International Journal of Poultry Science, 2011)
Since 2002, control of Newcastle Disease (ND) in South Africa has become complicated following the introduction of lineage 5d/VIId Newcastle Disease Virus (NDV) strain (locally known as “goose paramyxovirus” - GPMV). Commercially available ND vaccines appeared less effective. In this study, commercial and SPF hens in lay were vaccinated with La Sota vaccine and challenged with GPMV isolate to assess the effect of both vaccination and challenge on egg production. This study also compared the efficacy of cloacal and ocular routes of vaccination against challenge, following reports that cloacal vaccination offered a better protection against egg production losses than the oro-nasal route of vaccination. Vaccinated birds were fully protected (100%) against challenge by La Sota vaccine, but not against infection and replication of the virus, as birds showed varying degrees of macropathology and confirms the ability of virulent ND strains to infect and replicate even in vaccinated birds. Results also showed no clear difference in the protection of the birds against challenge with GPMV by either the cloacal and ocular routes of vaccination. Mmarginal to severe egg production drop was observed in both commercial and SPF birds after vaccination and challenge experiments.